American Civil War. - World Book, Inc. (Chicago, Ill. World Book, 2011)
"A history of the American Civil War, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Sources -- Juvenile literature